Attitude and practice of dental interns towards the use of rubber dam in different dental colleges of Kathmandu - Joshi, Barsha; Gautam, Suman; Joshi, Rojin; Khapung, Anju (Nepal Medical College Journal, 2023)
Rubber dam application during routine clinical procedures enhance the dental treatment. Attitude and practice of rubber dam application among dental interns during clinical procedure plays an important role in providing quality treatment and avoiding medicolegal consequences. The aim of this study was to determine the attitude and practice of dental interns towards rubber dam use. A questionnaire-based study was conducted using pre-structured questionnaire among 138 dental interns of three different colleges affiliated to Kathmandu University of Kathmandu District. The results showed that 97.1% study participants believe rubber dam gives good isolation, moisture control and safety. Positive attitude was shown by 55.1% of intern toward rubber dam use during all procedures and 64.5% during root canal treatment. Of the total, 73.2% believed they lacked training and 92.2% were willing to take more training. Most of the interns (85.5%) believe rubber dam as helpful tool. In conclusion, majority of the interns believe rubber dam gives good isolation, moisture control and safety but their lack of rubber dam use in clinical practice could be due to insufficient training, patients’ objection and extra time needed for placement. To overcome this, more trainings, preclinical and clinical demonstration and mandatory use during all clinical posting should be done in dental colleges.